Evaluación de probiótico (polimeve soluble) y microorganismos de montañas en cerdos en la etapa de acabado - Palma Gáleas, Arlenes Dayanara (2023)
To carry out this research, it was based on the use of probiotics and mountain microorganisms, these are formed from the fermentation of organic matter (earth) that has not been manipulated by humans for a minimum of 5 years in which fungi, bacteria, others are formed; these commonly generate bacteria such as Bactobacillus; One of the alternatives that probiotics and mountain microorganisms are commonly used is as a replacement for antibiotics; since these help to balance the intestinal microbiota, helping product parameters within swine production such as weight gain.For the investigation, an experimental unit of 15 pigs was used, where they are divided into three groups assigned to each treatment, the first group was assigned as a control treatment where it only received a conventional balanced diet and water where there was an average gain of 5kg during the experiment, the second group was assigned a conventional balanced diet with the inclusion of 20% probiotics plus water and had significant gains of an average of 11 kg and the third group was assigned a diet based on conventional balanced plus the inclusion of 20% of mountain microorganisms plus water and it could be observed that it had a gain range of 11kg. A completely randomized design was used, the variables evaluated were weight gain, cost - benefit, feed conversion, all these variables were recorded week by week for a month, since this research focuses on the use of these addictives in the stage just in pigs; For the management of the test, the pigs were fed twice a day and having the availability to drink water freely.